Tracking data and the conservation of the high seas: Opportunities and challenges. Issue 12 (25th September 2021) - Davies, Tammy E.; Carneiro, Ana P. B.; Campos, Bruna; Hazin, Carolina; Dunn, Daniel C.; Gjerde, Kristina M.; Johnson, David E.; Dias, Maria P.
Abstract: Biologging technology is rapidly advancing—scientists are obtaining data on movement and behaviour for a range of species, more accurately than ever before. With this information, it is possible to understand more about important areas and their connections across the open ocean including the high seas, beyond national jurisdictions. But an absence of a global governance framework has so far hindered a coordinated approach to conservation action on the high seas. We showcase a candidate high seas MPA in the Northeast Atlantic identified primarily from seabird tracking data and being taken forward under a regional process: the North Atlantic Current and Evlanov Seamount (NACES) MPA, under the OSPAR Commission. It provides a unique case study to learn about the intricacies of implementation when applying tracking information for conservation. From this, we identify the facilitating conditions and challenges faced from identification to designation and highlight actionable opportunities for future area‐based management of the high seas that will be made possible under a new agreement. Policy implications . The North Atlantic Current and Evlanov Seamount (NACES) MPA demonstrates the power of translating tracking data into usable geospatial knowledge to inform conservation and policy and provides an exemplar for a data‐driven approach to high seas conservation that can become a reality under the forthcoming governance framework (under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (known as the BBNJ Agreement)). This new agreement presents a unique conservation opportunity both for the application of tracking data to conservation outcomes and for the protection of migratory species. Abstract : The North Atlantic Current and Evlanov Seamount (NACES) MPA demonstrates the power of translating tracking data into usable geospatial knowledge to inform conservation and policy and provides an exemplar for a data‐driven approach to high seas conservation that can become a reality under the forthcoming governance framework (under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (known as the BBNJ Agreement)). This new Agreement presents a unique conservation opportunity both for the application of tracking data to conservation outcomes, and for the protection of migratory species.